Role of FGF10/FGFR2b Signaling in Mouse Digestive Tract Development, Repair and Regeneration Following Injury - Lv, Yu-Qing; Wu, Jin; Li, Xiao-Kun; Zhang, Jin-San; Bellusci, Saverio (Frontiers in Cell and Developmental Biology, 2019)
During embryonic development, the rudimentary digestive tract is initially a tube-like structure. It is composed of epithelial cells surrounded by mesenchymal cells. Reciprocal epithelial–mesenchymal interactions progressively subdivide this primitive tube into distinct functional regions: the tongue, the pharynx, the esophagus, the stomach, the duodenum, the small intestine, the cecum, the large intestine, the colon, and the anus as well as the pancreas and the liver. Fibroblast growth factors (Fgfs) constitute a family of conserved small proteins playing crucial roles during organogenesis, homeostasis, and repair after injury. Among them, fibroblast growth factor 10 (Fgf10) has been reported to orchestrate epithelial–mesenchymal interactions during digestive tract development. In mice, loss of function of Fgf10 as well as its receptor fibroblast growth factor receptor 2b (Fgfr2b) lead to defective taste papillae in the tongue, underdeveloped and defective differentiation of the stomach, duodenal, cecal, and colonic atresias, anorectal malformation, as well as underdeveloped pancreas and liver. Fgf signaling through Fgfr2b receptor is also critical for the repair process after gut injury. In the adult mice, a malabsorption disorder called small bowel syndrome is triggered after massive small bowel resection (SBR). In wild-type mice, SBR leads to a regenerative process called gut adaptation characterized by an increase in the diameter of the remaining small intestine as well as by the presence of deeper crypts and longer villi, altogether leading to increased intestinal surface. Intestinal stem cells are key for this regeneration process. Induction of Fgf10 expression in the Paneth cells located in the crypt following SBR suggests a critical role for this growth factor in the process of gut adaptation.